Impactos dos incentivos políticos institucionais sobre a melhoria dos serviços públicos municipais: evidências a partir do processo de reeleição dos prefeitos no Brasil - Amarante, José Carlos Araújo (2017)
This dissertation aims to investigate the impacts of the institutional political incentives, captured by the reelection process for the mayor, on the use of public resources in the indicators of coverage and quality of education and health services in Brazil. Based on the reputation-building model, the hypothesis is tested that the political agent in the attempt to maximize his political capital and thus increase the chances of remaining in elective positions tends, in a re-election system, align their interests to the preferences of the electorate to the detriment of their own preferences. Using the regression discontinuity design (RDD) method, a comparison of the performance of the mayors in first term during the management 20092012 with the results presented by mayors in second term in the same period. The evidences found indicate that mayors under reelection incentives present better performance in educational indicators, especially the increase in the coverage of early childhood education and, to a lesser extent, the index of development of basic education in the initial years of elementary education. On the other hand, in the health area, robust results were not identified that suggest that mayors in the first term perform better than those in second management.